Role of the Government Legislation Centre in the law-making process - Wróblewska, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The author analyzes the role of the Government Legislation Centre (RCL) in the law-making process. She identifies the main reasons for the establishment of this institution, combining them with the criticism of the current model of creating law. Increasing the effectiveness of the RCL involves the extension of its tasks.
Keywords: the creation of the law; the departmental model of creation; Government Legislation Centre